2019
DOI: 10.1039/c9sm00705a
|View full text |Cite
|
Sign up to set email alerts
|

Controlled reversible buckling of polydopamine spherical microcapsules: revealing the hidden rich phenomena of post-buckling of spherical polymeric shells

Abstract: Rich post-buckling phenomena of spherical polymeric shells are revealed by controlled reversible buckling of polydopamine spherical microcapsules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 81 publications
3
20
0
Order By: Relevance
“…In this work, nanobowls with diameters on the order of 35–40 nm were obtained. This is significantly smaller that the nanobowl dimensions typically reported, 260 nm to 4 μm, and roughly 1/4 that of the smallest previously reported PDA nanobowls, 150 nm. ,, In addition, the process reported here eliminates the need for the removal of hard templates and uses environmentally benign solvents.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…In this work, nanobowls with diameters on the order of 35–40 nm were obtained. This is significantly smaller that the nanobowl dimensions typically reported, 260 nm to 4 μm, and roughly 1/4 that of the smallest previously reported PDA nanobowls, 150 nm. ,, In addition, the process reported here eliminates the need for the removal of hard templates and uses environmentally benign solvents.…”
Section: Resultsmentioning
confidence: 58%
“…The numerous catechol and amine groups present in PDA endow it with excellent adhesion to many materials and provide a facile method for attachment of functional groups through the Michael addition or Schiff base reactions. Additionally, excellent biocompatibility and aromatic group content make PDA a promising material in biomedical and electrical applications. While spheres are by far the most studied shape of PDA, there have been some recent reports on the synthesis and properties of rod-like and tube-like , PDA nanostructures. Template-assisted techniques have been explored for the production of bowl-shaped PDA structures. However, all these methods resulting in large particles, on the order of 260 nm to 4 μm, are time-consuming, and the templates used or the solvents used to remove them increase the biocompatibility issues. Recently, biocompatible poly­(acrylic acid) nanoparticles have been used as templates for PDA nanobowl synthesis. While the particles produced are smaller on the order of 150–200 nm, and the materials used are biocompatible, the multiple-step fabrication process inherent in template-assisted synthesis still makes the preparation process complicated and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…This is different to the above-mentioned one-step polymerization methods, in which the surface concavity is formed directly in the polymerization process. Both hard templates [140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157] and soft templates [158][159][160][161][162][163][164][165][166] have been used for the preparation of dimpled polymer particles.…”
Section: Templating Methodsmentioning
confidence: 99%
“…It is worth emphasizing that dimpled polymer capsules can be conveniently fabricated by the "collapse" of the spherical capsules, which are formed by removing the core templates from the core-shell particles. [152][153][154][155][156][157] For example, Zhou and co-workers reported that polydopamine (PDA) nano/microcapsules could be readily produced by the formation of PDA on the template surface, followed by removal of the template. [152] When the diameter of the capsule reached to 2 mm, bowl-like capsules were observed due to collapse.…”
Section: Templating Methodsmentioning
confidence: 99%
See 1 more Smart Citation